Epidemiological, clinical and laboratory profile of dermatopathies of household dogs and cats in a semi-arid region of Northeast Brazil (Research, Society and Development, 2021)
The present study aims to determine the epidemiological, clinical and laboratorial profile of the dermatopathies that affect dogs and cats living in a semi-arid area in the Northeast of Brazil. Seventy-eight dogs and cats consulted at the Veterinary Hospital with dermatological complaints were included in this study. Skin lesions were characterized with respect to morphology, appearance, and distribution, an epidemiological questionnaire was applied, and samples were collected for complementary examination. The diagnosis was confirmed by parasitological and microbiological tests.  There was a predominance of the canine species (93.6%), of young animals (46.3%), and of animals of undefined breeds (61.5%).  It was observed that 29.5% of the affections were of fungal aetiology, 14.1% were bacterial, 3.9% were scabies. In 5.1% of the cases there were associations between different pathogens, and in 47.4% the laboratory examination was negative for the pathogens investigated. The most frequent clinical manifestations included alopecia (74.4%), pruritus (61.6%) and erythema (43.6%), distributed mainly in the dorsal-ventral region (36.1%) or even disseminated (43.1%). With respect to One Health, 51.3% (40/78) of the owners reported that they did not know what "zoonoses" were.  Dermatopathies have been shown to be important disorders, especially the mycotic and bacterial diseases. Atypical cases of infections motivated by pathogens little described in the literature as etiologic agents of dermatopathies in dogs and cats were observed.